Impact of Foreign Institutional Investments on Stock Market Volatility in India - Dadhich, Gaurav; Chotia, Varun; Chaudhry, Omvir (Indian Journal of Finance, 2015)
India is being viewed as a potential opportunity by investors, with the economy having the capacity to grow tremendously. Buoyed by exceptional support from the country's government, the FII sector in India looks set to prosper, and the outlook looks extremely promising. In this paper, an attempt was made to study the volatility patterns in Indian markets through properties such as volatility clustering, leverage effect. This paper tried to examine FII flows in Indian securities market and assessed the impact of foreign institutional investment on Indian stock market volatility. Effect of news in the first moment was modeled with the help of ARCH-GARCH process and the change over 24 hours (from a closing rate to a closing rate) was measured for a period from 2004-2014. Our analysis revealed the persistence of volatility and confirmed the leverage effect in Indian securities market. We observed that FIIs contributed significantly to the Indian stock market volatility. The coefficient of gross purchase was significant, suggesting that a greater volatility in gross purchase by FIIs could have greater implications for the volatility of stock indices during 2004-2014 in comparison to gross sales by FIIs.